Persaingan Usaha Antara Ojek Pangkalan (Konvensional) Dan Ojek Online - Maya Aprillya Putri; Teddy Prima Anggriawan; Aldira Mara Ditta Caesar Purwanto (Universitas Katolik Widya Karya Malang, 2023)
The development of communication media has led to the presence of applications to order online motorcycle taxi transportation services. The application can be easily downloaded via PlayStore or similar applications. Therefore, the purpose of this discussion is to find out how business competition is between conventional ojek and online ojek business actors. In Indonesia there are several online motorcycle taxi service providers such as Grab, Gojek, and Maxim. The services provided are not only in the form of online motorcycle taxi services, but also in the form of food delivery services (grabfood), online shopping services (grabmart), package delivery (grabexpress) and other services. It is known that there are problems between online motorcycle taxis and conventional motorcycle taxis that have occurred, such as the beating by a conventional motorcycle taxi driver against a Gojek driver in Bojongsoang, Bandung. In this study, the authors used a qualitative type of research because it discussed business competition between business actors. Meanwhile, the nature of the research used is descriptive research. The research approach used by the author in this journal is included in the type of statutory approach and the Case Approach.